1997
DOI: 10.1111/j.1540-8159.1997.tb03916.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with Thera DR Rate‐Drop Response Pacing Algorithm in Carotid Sinus Syndrome and Vasovagal Syncope

Abstract: This study examined the effectiveness of cardiac pacing using the Thera DR rate-drop response algorithm for prevention of recurrent symptoms in patients with carotid sinus syndrome (CSS) or vasovagal syncope. The algorithm comprises both diagnostic and treatment elements. The diagnostic element consists of a programmable "window" used to identify heart rate changes compatible with an evolving neurally mediated syncopal episode. The treatment arm consists of pacing at a selectable rate and for a programmable du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(27 citation statements)
references
References 26 publications
0
25
0
2
Order By: Relevance
“…Pacemaker therapy was more effective than in other studies [2][3][4][5] in which syncope recurred in 18% to 50% of patients. We think that a possible explanation for these better results was the different selection of patients.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Pacemaker therapy was more effective than in other studies [2][3][4][5] in which syncope recurred in 18% to 50% of patients. We think that a possible explanation for these better results was the different selection of patients.…”
Section: Discussionmentioning
confidence: 48%
“…In a tilting study, 1 syncope was not prevented by atropine or pacing. A few observational, nonrandomized studies [2][3][4] have suggested a possible benefit from pacing, but syncope recurred in 18% to 50% of patients over a follow-up ranging from 6 to 50 months. In a recent randomized, controlled trial, 5 there was an 84% reduction in risk of syncope in pacemaker patients compared with patients without pacemakers, but syncope still recurred in 22% of patients during a 2-month follow-up.…”
mentioning
confidence: 99%
“…Duration of CSM should be between 5-10 seconds [2,3,10,11,33,38]. No comparative studies have been done to assess the optimum duration of CSM; however, some suggest that 10 seconds is preferable if one requires the reproduction of symptoms as an endpoint [11].…”
Section: Diagnostic Assessmentmentioning
confidence: 98%
“…These functions allow pacing to occur at an accelerated rate in the face of impending syncope. The term "hysteresis" refers to a function that allows the pacing rate to exceed the device's lower rate limit for a programmable period of time [16]. For instance, if a pacemaker was programmed with 50/80 hysteresis, pacing would not begin until the intrinsic heart rate dropped to less than 50 beats/minute.…”
Section: Permanent Pacemaker Implantationmentioning
confidence: 99%